Pemanfaatan Teknologi Wireless dan Mobile Network Berbasis 5G Untuk Pemerataan Akses Jaringan di Indonesia - Eka Putra, Fauzan Prasetyo; Ubaidillah Solichin, Ach.Maulidani; Wildanul Hakim, Moh.Nuril; Ramadhan, Mohammad Taufiq (Fakultas Teknik Universitas Hamzanwadi, 2025)
This study discusses the utilization of wireless and mobile network technologies based on 5G as a strategic solution to promote equitable access to network connectivity in Indonesia. Given Indonesia's vast and diverse geographical context, 5G offers advantages in terms of high speed, low latency, and spectral efficiency, enabling more inclusive connectivity, particularly in remote and underserved areas. The study also examines the application of supporting technologies such as Wireless Sensor Networks (WSN) and Reconfigurable Intelligent Surfaces (RIS) to expand signal coverage and enhance network quality. The research employs a descriptive-qualitative approach with secondary data analysis derived from various reputable scientific publications, official reports from BAKTI Kominfo, and relevant national regulatory policies. The data were analyzed thematically and evaluatively to identify the potential, challenges, and implementation strategies of 5G in addressing digital access disparity. The results indicate that the integration of 5G technology with WSN and RIS has a positive impact on improving digital access across sectors such as education, healthcare, economy, and governance. Nonetheless, challenges such as limited infrastructure, suboptimal regulations, and digital literacy gaps remain significant barriers. Therefore, multisectoral collaboration is needed in infrastructure development, policy reform, and community empowerment to achieve inclusive and sustainable network accessibility.